Devonian Carbonate of Telen River, East Kalimantan - Fransiskus Sugiaman; Ludy Andria (Berita Sedimentologi, 1998)
BSc Thesis submitted to Bandung Institute of Technology, 1990In 1925, the Dutch Colonial Government sent a scientific expedition team to East Kalimantan, which was called "Midden Oost Borneo Expeditie" and led by H. Witkamp. The expedition collected rock samples from Telen River, a tributary of Mahakam River. In 1940, L. Rutten analyzed the rock samples and found Devonian fossils, which were known as the oldest fossils in western part of Indonesia. The fossils were found in a dark, crystalline limestone and Marks (1951) included the limestone into Danau facies. The existence and location of the limestone is often mentioned and cited by many geologist, such as Van Bemmelen (1949), Marks (1957), Sartono (1970), and Soejono (1988), since it is assumed as a classical stratigraphic location.The location of the Devonicn limestone had never been revisited since the Dutch expedition, due to its remote location and difficult accessibility. The distribution of the Devonian limestone and its stratigraphic correlation with other units were still a mystery. Noticing the limitation of the geological information on the Devonian limestone, the Association of Geology Students "GEA" from Bandung Institute of Technology (ITB) organized a scientific expedition, which is called Devonian Expedition 1989. Field work was conducted in October to November 1989.